Unilateral modification of Bank Loan Contracts under Hungarian Law - Dudaš, Atila (Zbornik radova Pravnog fakulteta u Novom Sadu, 2018)
The issue of legality of stipulations enabling banks and other financial institutions to modify loan contracts unilaterally had its evolution in Hungarian law, too. What is peculiar to Hungarian law, if considered parallel to Serbian law, is that Hungary, at the eruption of the global financial crisis, or to be more precise, somewhat later, when the number proceedings for the annulment of loan contracts became significant, had specific legislation on this subject the matter, the 1996 Law on Credit Institutions and Financial Enterprises (Hpt.). The Law, in its text applicable until 1st January, 2004, considered valid stipulations enabling unilateral modification of loan contracts. However, it did not prescribe conditions under which such clause may be considered valid, but left freedom to parties to regulate it. The consequence of freedom of contract was that such stipulations have regularly been formulated, so that financial organizations had wide discretion in its application. Realizing the danger of abuse, the legislator changed the Law. The new text, effective from 1st January, 2010, contains considerably more detailed regulations and prescribes stringent conditions of validity of a clause on the right to amend the terms of the loan unilaterally. However, even with the more detailed regulations, a number of issues remained open that ultimately needed to be addressed by the supreme judicial instance, i.e. the Curia. It was first attempted in the judgment of the Curia in the so-called Partiscum case from 2011, but the most significant interpretation of the conditions under which stipulating the right to unilaterally amend the contract, was given in the decision no. PK 2/2012. (XII.10) of the civil law session of the Curia. The Curia stated that such stipulation shall be considered valid, if it is unambiguously and clearly formulated; if the reasons of unilateral modifications are enumerated; if they are determined objectively; if they have a real impact on the elements that influence the interest rate, fees and expenses in connection with the contract and that the scope of changes in the contract is proportional to the scope of changes of relevant circumstances; that the stipulation was transparent for consumers, and if the clause is applicable to the consumer as well, if the relevant circumstances change to his advantage. The requirements of clear and unambiguous formulation and transparency was further clarified in Curia’s decision no. 2/2014. PJE. The Curia stated that for the fulfillment of this condition it is not satisfactory that the wording of the stipulation is correct linguistically and grammatically, but it requires that is should be formulated so as to enable the consumer to understand and assess its possible economic consequences. The adoption of this decision was necessary because the ECJ delivered its decision in the Kásler case (C-26/13) in the meantime, which complements the interpretation of Art. 4. sec. 2 of the Directive 93/13/EEC on unfair terms in consumer contracts. The final stage in the evolution of the legal framework of the right to unilateral modifications of loan contracts in Hungarian law, was the enactment of the Law no. XXXVIII of 2014, which raised the content of the conclusions of the Curia to the level of general legal act. The law sparked much criticism regarding its constitutionality: concerns were raised in relation to the establishment of a legal presumption of unfairness of contractual clauses and provisions of general business conditions of banks that explicitly enabled them to change loan contracts unilaterally. It is stated correctly in the literature that by this means the consequences of incomplete and inadequate legal framework were subsequently shifted on financial institutions, even if at the time of conclusion of the contract, or when the general business conditions were in force, they were in line with the effective regulations. The Law has, however, sustained the control of constitutionality. In Hungary today, unilateral modification of banking loan contracts is subject to a very strict legal regime. According to the amendments of the Consumer credit act from 2014 loans with repayment period shorter than three years cannot be unilaterally modified to the detriment of the consumer at all. Contracts with longer repayment period can be modified to the detriment of the consumer up to five times, while the interest rate must remain unaltered for at least three years after each modification. In addition, the range in which financial organizations could increase the interest rate is controlled by the Hungarian Central Bank by disclosing indices officially in the range of which the interest rate could be altered.